2014
DOI: 10.1088/0264-9381/31/4/045006
|View full text |Cite
|
Sign up to set email alerts
|

The role of nonmetricity in metric-affine theories of gravity

Abstract: The intriguing choice to treat alternative theories of gravity by means of the Palatini approach, namely elevating the affine connection to the role of independent variable, contains the seed of some interesting (usually under-explored) generalizations of General Relativity, the metric-affine theories of gravity. The peculiar aspect of these theories is to provide a natural way for matter fields to be coupled to the independent connection through the covariant derivative built from the connection itself. Adopt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…For this case we will just add the Gauss-Bonnet term which we know does not produce any ghost for the metric perturbations. Adding non-metricity as well as torsion has been studied in [21]. The author has shown that at the second order gravity level, connection has no dynamics which is same as the results in [14].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For this case we will just add the Gauss-Bonnet term which we know does not produce any ghost for the metric perturbations. Adding non-metricity as well as torsion has been studied in [21]. The author has shown that at the second order gravity level, connection has no dynamics which is same as the results in [14].…”
Section: Introductionmentioning
confidence: 87%
“…The other approach, which is more similar to [25], is to write all the possible terms constructed by non-metricity and torsion in addition to the metric itself. This second approach was done in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The work was supported by the Estonian Research Council through the Institutional Research Funding project IUT02-27 and the Personal Research Funding project PUT790 (start-up project), as well as by the European Regional Development Fund through the Center of Excellence TK133 "The Dark Side of the Universe". Let us calculate the contractions of G λ µν ω σρ , defined by (16). A straightforward calculation yields…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In this paper, we will use a formalism called metricaffine geometry, in which the metric and the connection are independent variables [35][36][37][38][39][40][41]. We consider theories given only by the curvatures, but not by the function of the connections such as torsions.…”
Section: Introductionmentioning
confidence: 99%